2022
DOI: 10.1038/s41467-022-34641-7
|View full text |Cite
|
Sign up to set email alerts
|

The composition and structure of the ubiquitous hydrocarbon contamination on van der Waals materials

Abstract: The behavior of single layer van der Waals (vdW) materials is profoundly influenced by the immediate atomic environment at their surface, a prime example being the myriad of emergent properties in artificial heterostructures. Equally significant are adsorbates deposited onto their surface from ambient. While vdW interfaces are well understood, our knowledge regarding atmospheric contamination is severely limited. Here we show that the common ambient contamination on the surface of: graphene, graphite, hBN and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 71 publications
2
22
0
Order By: Relevance
“…They showed that the pattern is formed by adsorption of linear alkanes with a length of 20–26 carbon atoms aligned along the zigzag direction of the graphene surface. According to Pálinkás et al, [ 39 ] the periodicity of these stripes (5 nm) at room temperature is equal to the length of the linear alkanes. Consequently, the stripes reflect the orientation of the armchair direction of the graphene lattice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…They showed that the pattern is formed by adsorption of linear alkanes with a length of 20–26 carbon atoms aligned along the zigzag direction of the graphene surface. According to Pálinkás et al, [ 39 ] the periodicity of these stripes (5 nm) at room temperature is equal to the length of the linear alkanes. Consequently, the stripes reflect the orientation of the armchair direction of the graphene lattice.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the adsorbates forming different domains, we also expect stripe-like patterns to form on graphitic surfaces upon storage. [29][30][31][32][33][34][35][36][37][38][39] Based on the results of our previous study, [40] we analyzed the effect of plasma treatment on the stripe-like patterns by using the second flexural phase images, as shown in Figure 4. The corresponding lateral drive-amplitude images, in which the stripe-like patterns are also visible, are shown in Figure S6 (Supporting Information).…”
Section: Stripe-like Adsorbate and Island Formation Successively Remo...mentioning
confidence: 99%
See 2 more Smart Citations
“…33,34 A recent study identified, using low-temperature scanning tunneling microscopy (STM) and other measurements, that the contaminants are normal alkanes with lengths of 20−26 carbon atoms when freshly-cleaved samples of two-dimensional (2D) materials were stored in plastic containers. 35 from the plastic container; the contaminants from ambient are likely much more complex. All these findings suggest that the airborne hydrocarbon contaminates are likely one of the sources of inconsistent surface potentials of graphite previously reported in the literature.…”
Section: ■ Introductionmentioning
confidence: 99%